Estimation of the Cholesky Multivariate Stochastic Volatility Model Using Iterated Filtering - Szczepocki, Piotr (Estymacja wielowymiarowego modelu stochastycznej zmienności z dekompozycją Choleskiego przy użyciu iterowanej filtracji, 2023)
Aim: The paper aims to propose a new estimation method for the Cholesky Multivariate Stochastic Volatility Model based on the iterated filtering algorithm (Ionides et al., 2006, 2015). Methodology: The iterated filtering method is a frequentist-based technique that through multiple repetitions of the filtering process, provides a sequence of iteratively updated parameter estimates that converge towards the maximum likelihood estimate. Results: The effectiveness of the proposed estimation method was shown in an empirical example in which the Cholesky Multivariate Stochastic Volatility Model was used in a study on safe-haven assets of one market index: Standard and Poor’s 500 and three safe-haven candidates: gold, Bitcoin and Ethereum. Implications and recommendations: In further research, the iterating filtering method may be used for more advanced multivariate stochastic volatility models that take into account, for example, the leverage effect (as in Ishihara et al., 2016) and heavy-tailed errors (as in Ishihara and Omori, 2012). Originality/Value: The main contribution of the paper is the proposition of a new estimation method for the Cholesky Multivariate Stochastic Volatility Model based on iterated filtering algorithm This is one of the few frequentist-based statistical inference methods for multivariate stochastic volatility models.
Econometrics = Ekonometria, 2023, Vol. 27, No. 4, s. 44-58
Keywords: multivariate stochastic volatility; iterated filtering; particle filters; Cholesky Multivariate Stochastic Volatility; wielowymiarowe modele stochastycznej zmienności; iterowana filtracja; filtry cząsteczkowe